THE URGENCY OF ISLAMIC EDUCATION FOR MENTAL HEALTH AT THE FACULTY OF ISLAMIC STUDIES, ISLAMIC UNIVERSITY 45 BEKASI - Siti Khodijah; Qonita Amanda Putri; Maragustam, Maragustam; Akmal Rizki Gunawan (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This study examines the importance of Islamic religious education on students' mental health at Universitas Islam 45 Bekasi, focusing on integrating faith values and worship practices into the education system. It aims to investigate how Islamic religious education impacts students' mental well-being, stress resilience, and personal development. Using qualitative methods, including surveys and interviews, the study shows that Islamic religious education significantly contributes to students' mental health by providing spiritual support, fostering community, and enhancing personal growth. The results indicate that daily worship practices and incorporating Islamic teachings into the curriculum positively affect students' mental health, promoting calmness and stress management. The conclusion emphasizes the crucial role of Islamic religious education in supporting students' mental well-being, suggesting the need for its integration into higher education systems to foster a holistic development approach.